The Influence of Work Life Balance and Work Discipline on Employee Performance - Triana, Nabila; Suratman, Andriyastuti (Selekta Manajemen: Jurnal Mahasiswa Bisnis & Manajemen, 2022)
Often companies provide an excessive number of tasks which results in decreased of work productivity and discipline for employees. This shows that an individual has difficulty in balancing his personal life and work. This study aims to examine and analyze the influence of work life balance and work discipline on employee performance through job satisfaction. This research gained 75 respondents as a sample from PT. Indonesia Morowali Industrial Park (IMIP). The data collection of quantitative method uses a survey with a questionnaire via Google Form. Data analysis used t-test, F test, simple linear regression analysis, multiple linear regression analysis, and path analysis using SPSS 21 software. The results of this study reveal a positive and significant influence between the work-life balance on job satisfaction, work discipline on job satisfaction, work-life balance on employee performance, work discipline on employee performance, and job satisfaction on employee performance. Yet, the indirect influence of work life balance and work discipline on employee performance through job satisfaction are greater than the direct influence. Setelah itu tuliskan keterbatasan penelitian. This research implies that work-life balance can be improved by paying attention to satisfaction to increase employee performance. Work discipline can be increased by paying attention to sanctions and time efficiency to increase employee performance. Job satisfaction can be enhanced by paying attention to the environment and payment of employee, last employee performance can be improved by taking into account the responsibility.